Electric Vehicle Charging Station Location by Applying Optimization Approach - Shoushtari, Farzaneh; Talebi, Mohammadamin; Rezvanjou, Seyedkian (International journal of industrial engineering and operational research, 2024)
The rapid growth in electric vehicle (EV) adoption brings about the need for an efficient and well-planned network of charging stations. This paper aims to address the problem of determining optimal locations for EV charging stations using an optimization approach. Through an extensive literature review, the existing research on EV charging station location selection is discussed and analyzed. A novel methodology is proposed and implemented, considering factors such as urban infrastructure, accessibility, demand patterns, and operational cost. The numerical results demonstrate the effectiveness of the proposed approach in finding optimal charging station locations. The paper concludes with recommendations for the future expansion of EV charging station networks and the potential benefits for EV owners and the environment.